2012
DOI: 10.1103/physreva.85.053645
|View full text |Cite
|
Sign up to set email alerts
|

Vortex trimer in three-component Bose-Einstein condensates

Abstract: Vortex trimer is predicted in three-component Bose-Einstein condensates (BEC's) with internal coherent couplings. The molecule is made by three constituent vortices which are bounded by domain walls of the relative phases. We show that the shape and the size of the molecule can be controlled by changing the internal coherent couplings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…As real QCD has SU (3) symmetry, our next step will be the confinement of 1/3 quantized vortices in threecomponent BECs, for which a baryon was constructed numerically in Ref. [30,31]. While we have shown confinement of charged bosons, the recently highlighted duality between vortices and fermions [32] The baryonic molecule for g 12 > 0 at the equilibrium is static because the inter-vortex repulsion is canceled by the confinement force by the soliton.…”
Section: Discussionmentioning
confidence: 99%
“…As real QCD has SU (3) symmetry, our next step will be the confinement of 1/3 quantized vortices in threecomponent BECs, for which a baryon was constructed numerically in Ref. [30,31]. While we have shown confinement of charged bosons, the recently highlighted duality between vortices and fermions [32] The baryonic molecule for g 12 > 0 at the equilibrium is static because the inter-vortex repulsion is canceled by the confinement force by the soliton.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent theoretical results on vortex lattice conformations have shown that multi-component Bose-Einstein condensates are far from being just a trivial extension of the single component case. In fact, adding a component brings a diversity of possible configurations never found in a onecomponent system, such as amorphous conformations, square lattices and bound states, including overlapped vortices, vortex dimers and molecules [18][19][20][21][22]. Some of these conformations suggest that the interaction between vortices can be nonmonotonic with respect to the intervortex distance.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to date, the interaction between vortices in the simplest multi-component BEC is known only in specific limits of scale, by either assuming inter-vortex distances much greater than the healing length [23] or considering the interaction energy near the vortex peak in the Thomas-Fermi regime [24]. As it turns out, the asymptotic behavior does not account for all conformations found [19][20][21][22]. Furthermore, the generalization of these analytical approaches to more complex cases with more components or even with a different kind of inter-component particle-particle interaction seems to be highly non-trivial.…”
Section: Introductionmentioning
confidence: 99%
“…The subtle interplay between the various interactions suggests that when such a frustrated system is set in rapid rotation, highly unconventional vortex lattices may appear in the rotating ground state. So far, studies of vortices in Rabi-coupled three-component BECs have focused on states with only a few vortices and have demonstrated, for example, the existence of stable vortex trimers [29][30][31][32]. The possible structures of ground-state vortex lattices in these systems, however, have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the system is set into rotation about the z axis with angular frequency Ω, we write the two-dimensional GrossPitaevskii (GP) energy functional [30] in the rotating frame of reference as…”
Section: Theoretical Frameworkmentioning
confidence: 99%